Juridical Review of the Criminal Act of Corruption in Selling Subsidized Fertilizer to Unauthorized Recipients According to the Definitive Plan for Group Needs by Subsidized Fertilizer Retailers (Case Study in Karo Regency) - Sitepu, Deni Randa; Siregar, Mahmul; Alsa, Abdul Aziz (Jurnal Hukum Replik, 2024)
This study examines the problem of misuse of subsidized fertilizers in Indonesia, especially in Karo Regency, with a focus on the distribution mechanism, the application of elements of corruption, and legal protection for disadvantaged farmers. Using a descriptive empirical legal research method, this study found that the distribution of subsidized fertilizers is regulated by Permentan No. 10/2022 and Permendag No. 04/2023, with sales by retail kiosks to unauthorized parties categorized as a criminal act of corruption based on Law No. 31/1999 in conjunction with Law No. 20/2001. Legal protection for disadvantaged farmers includes the right to report cases, file civil lawsuits, and obtain legal assistance from the government. This study concludes that although the distribution mechanism is strictly regulated, irregularities still occur, so that system improvements and stricter law enforcement are needed to ensure that subsidies are on target and protect farmers' rights